Efficacy and Safety of a Novel Herbal Medicine in the Treatment of Irritable Bowel Syndrome: A Randomized Double-Blinded Clinical Trial - Ghasem Bordbar; Mohammad Bagher Miri; Mahmoud Omidi; Saeed Shoja; Malihe Akhavan (Gastroenterology Research and Practice)
Background. The unresponsiveness to conventional pharmacological treatments and their side effects have led patients with irritable bowel syndrome (IBS) to use complementary and alternative medicine such as herbal remedies. Beside, Zataria multiflora Boiss (ZM), Trachyspermum ammi L. (TA), and Anethum graveolens L. (AG) are being used as an antiseptic, carminative, and antispasmodic in traditional medicine. This trial investigated the efficacy and safety of a combination of ZM, AG, and TA essential oils in the treatment of IBS. Method. The present study was a randomized double-blind clinical trial with parallel groups in Iran. Patients in the control arm received three tablets of 10 mg hyoscine butylbromide daily for two weeks, and the intervention arm was daily treated with two 250 mg softgel capsules containing 180 mg of essential oils of ZM, AG, and TA for two weeks. Primary outcomes were the response rates based on the IBS Symptom Severity Scale (IBS-SSS), IBS Adequate Relief (IBS-AR), and IBS Global Assessment Improvement (IBS-GAI) at the end and two weeks after the end of the intervention. Secondary outcomes were the improvement rates in IBS-SSS scores, improving the quality of life, safety, and tolerability. Results. The posttreatment improvement percentage based on IBS-AR, IBS-GAI, and IBS-SSS scales was 83.9%, 75%, and 87% in the intervention group and 37.9%, 27.5%, and 34.4% in the control group, respectively (P<0.001). Also, the improvement of the quality of life in the herbal medicine arm was significantly more than that in the control arm (P<0.001). Conclusions. According to the results, the herbal medicine investigated in this study can be considered an appropriate alternative treatment for IBS.